Teachers’ Narratives on Preparedness and Content Delivery in the Implementation of the Matatag Curriculum - Motel, Greselah M (Edu Berkah Khatulistiwa, 2025)
The global education sector struggles with curriculum transitions, especially in low- and middle-income nations, due to poor instruction and teacher shortages. The 2024 EDCOM 2 report, *Miseducation: The Failed System of Philippine Education*, identifies systemic failures and provides forty recommendations for reform, focusing on resources, support systems, and teacher training. This study examines teachers' experiences with the Matatag Curriculum, reinforcing the need to address these challenges for effective implementation and professional development. This study explores the lived experiences of teachers regarding their preparedness and content delivery in the implementation of the Matatag Curriculum. The study used the phenomenological design under qualitative approach and conducted one-on-one interview using semi-structured interview guide that targeted (10) ten Grade 4 teachers in Pulong Sta. Cruz Elementary School as the participants of the study. The findings of this study reveal that the implementation of the Matatag Curriculum proved to be a challenging and overwhelming experience for many teachers. This shift requires teachers to adapt to new methodologies, teaching strategies, and content delivery approaches, posing both opportunities and challenges. Understanding these dynamics is crucial in ensuring the successful implementation of the curriculum. From the initial training phase to the first weeks of execution, educators encountered numerous challenges that made adaptation to the curriculum's demands difficult. These included a lack of comprehensive preparation and the need to develop new teaching methods suited to the curriculum. To address these challenges, the researcher recommended that teachers should be provided with comprehensive and hands-on training sessions that focus on practical application and real-life classroom scenarios. Also, the Department of Education should provide sufficient and timely learning resources, such as complete and aligned textbooks, teachers' manuals, and activity sheets that include comprehensive lessons. It is also strongly recommended that schools in the City Schools Division of Santa Rosa City adopt the crafted Learning Action Cell (LAC) Session Guide to enhance teacher effectiveness and productivity.